2009
DOI: 10.1590/s1516-35982009000600006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição de Lactobacillus sp. na ensilagem de cana-de-açúcar

Abstract: RESUMO -Objetivou-se avaliar o efeito de aditivos microbianos com bactérias heterofermentativas ou homofermentativas sobre as características de silagens de cana-de-açúcar (Saccharum spp.). A cana-de-açúcar foi inoculada com as bactérias Effect of the addition of Lactobacillus sp. in sugarcane silagesABSTRACT -This study was aimed to evaluate the effect of microbial additives containing hetero fermentative or homo fermentative bacteria on the characteristics of sugarcane silages. Sugarcane was inoculated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…For example, previous studies have shown that L. plantarum reduces (Ávila, Valeriano, et al, 2010;Carvalho et al, 2015;Itavo et al, 2010), has no effect Freitas, Pereira, Rocha, Detmann, et al, 2006;Pedroso et al, 2008), and increases ethanol concentration, DM loss, and aerobic stability of sugarcane silage (Pedroso et al, , 2008Valeriano et al, 2009).…”
mentioning
confidence: 99%
“…For example, previous studies have shown that L. plantarum reduces (Ávila, Valeriano, et al, 2010;Carvalho et al, 2015;Itavo et al, 2010), has no effect Freitas, Pereira, Rocha, Detmann, et al, 2006;Pedroso et al, 2008), and increases ethanol concentration, DM loss, and aerobic stability of sugarcane silage (Pedroso et al, , 2008Valeriano et al, 2009).…”
mentioning
confidence: 99%
“…This has possibly elapsed from effluent production and leaching, which, however, have not been quantified in this study. According to Valeriano et al (2009), the levels of ash in sugar cane are usually low, and the oscillations in gray levels can be used to estimate values of DM loss during fermentation. Teixeira et al (2008) found pH variation of 3.7 to 4.1 for elephant grass silage; and as observed in this study, where the pH was 3.4 to 4.0, the variation and the silage additive with cornmeal presented the best pH, 3.93, when compared to other additives.…”
Section: Resultsmentioning
confidence: 99%
“…The CP content differed only when additive with urea the 2% natural matter, where there has been an increase of 19.78% of CP in DM, corroborating with results found by Pedroso et al (2007) who found that DM loss of 6.56% and additions of 19.5% to CP when they made the use of urea (1.5% in DM) as a feed additive for sugar cane silage. The increase in CP of dough before being compared to clamped silage material, is probably related to the use of soluble carbohydrates, causing a percentage increase in levels of CP (VALERIANO et al, 2009). The losses of NDF, TDN and ASH showed no statistical differences among treatments.…”
Section: Resultsmentioning
confidence: 99%
“…According to Valeriano, Pinto, Ávila, Evangelista, Tavares & Schwan (2009), "this increase during silage occurs mainly as a result of the use of soluble carbohydrates, causing a percentage increase in raw protein content".…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to fermentation of structural carbohydrates (Reyes, Montañez, Rodríguez, Ruiz, Salcedo, Avellaneda & Quintana, 2012). Moreover, Kung Jr and Stanley (1982), cited by Valeriano et al (2009) mentions that "percentage increases of the fibrous fraction in silage material increases in relation to the original material can be seen, as a result of water-soluble constituent losses", together with effluents produced during fermentation (Bolsen, 1995, cited by Valeriano et al, 2009 or by gas losses.…”
Section: Discussionmentioning
confidence: 99%